Analisis Kinerja dan Karakterisasi Axially Asymmetric SRR sebagai Penyerap GEM C-Band - Rasheed Abdurrahman Mulyadi; Muhammad Agy Ramdhan; Budi Syihabuddin; Levy Olivia Nur (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
In the last decade, planar electromagnetic (EM) wave absorbers began to be widely studied. This type of EM wave absorber is thin, flexible, and easy to fabricate, which allows absorber to be used in new future applications. Split Ring Resonators (SRR) are one of many forms of absorber that is known to have an excellent absorbance performance. In this paper, square patch absorber, Axial Symmetric SRR (AS-SRR), and Axially Asymmetric SRR (AAS-SRR) are designed and observed in C-Band. From the simulation results, we obtained a square cell size of 30 mm, AS-SRR of 20 mm, and AAS-SRR of 18 mm. The three forms can reach absorption rates above 92%, with a bandwidth of 0.055 GHz, 0.076 GHz, and 0.081 GHz, respectively. Furthermore, the AAS-SRR design parameters were characterized, and the main parameters that influence the bandwidth and resonant frequency are the resonator length and resonator thickness. The maximum bandwidth of the characterization is 0.087 GHz.